2012
DOI: 10.1093/cid/cis902
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Comparative Study of Knowlesi, Falciparum, and Vivax Malaria in Sabah, Malaysia: High Proportion With Severe Disease From Plasmodium Knowlesi and Plasmodium Vivax But No Mortality With Early Referral and Artesunate Therapy

Abstract: Plasmodium knowlesi is the commonest cause of severe malaria at QEH, with parasitemia the major risk factor for severity. Early referral and treatment with artesunate was highly effective for severe malaria from all species and associated with zero mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
486
2
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(529 citation statements)
references
References 30 publications
33
486
2
8
Order By: Relevance
“…Therefore, it is important to examine P. knowlesi accurately as the erythrocytic replication period is the shortest (24 h) among the species, which may lead to death of the patient. It has been reported that P. knowlesi was the commonest severe infection occurring in the main hospital in Kota Kinabalu (Hospital Queen Elizabeth), Sabah (10,45). As such, this study suggests that our multiplex primers could be of great potential as an alternative method as they can distinguish P. knowlesi from other malarias.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Therefore, it is important to examine P. knowlesi accurately as the erythrocytic replication period is the shortest (24 h) among the species, which may lead to death of the patient. It has been reported that P. knowlesi was the commonest severe infection occurring in the main hospital in Kota Kinabalu (Hospital Queen Elizabeth), Sabah (10,45). As such, this study suggests that our multiplex primers could be of great potential as an alternative method as they can distinguish P. knowlesi from other malarias.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, the RDT also may not be suitable for mixed infections, as it only reports the absence or presence of Plasmodium sp. (8) and performs poorly in P. knowlesi cases (10).…”
Section: Introductionmentioning
confidence: 97%
“…3 Meanwhile, retrospective clinical analyses of severe knowlesi malaria reveal that parenteral artesunate treatment conferred faster parasite clearance and low case-fatality relative to quinine, whereas early treatment with artesunate resulted in no mortality rate. 3,18 Consistently, in vitro drug susceptibility study has shown that P. knowlesi exhibited high sensitivity to artemisinins, whereas sensitivities to chloroquine and mefloquine were lower. 19 Therefore, parenteral artesunate has been recommended by the World Health Organization (WHO) as the treatment of choice for severe knowlesi malaria.…”
Section: Discussionmentioning
confidence: 76%
“…This zoonotic malaria may frequently cause severe or even life-threatening disease [46,47]. The main source of metabolic energy for the erythrocytic stages of the parasite Plasmodium knowlesi in macaques seems to be glycolysis [48,49] but,this species, to our knowledge, has not been associated with hypoglycaemia in humans [47].…”
Section: Dysglycaemia and Other Plasmodium Speciesmentioning
confidence: 93%